An example of the importance of labels and fieldbooks in scientific collections: A freshwater sponge misunderstood for a marine new genus and species - Pinheiro, Ulisses; Nicacio, Gilberto; Muricy, Guilherme (Zootaxa, 2015)
The demosponge genus Crelloxea Hechtel, 1983 was created to allocate a single species, Crelloxea spinosa Hechtel, 1983, described based on specimens collected by Jacques Laborel in northeastern Brazil in 1964 and deposited at the Porifera Collection of the Yale Peabody Museum. The genus Crelloxea was originally defined as "Crellidae with dermal and interstitial acanthoxeas and acanthostrongyles, with skeletal oxea and without microscleres or echinators" (Hechtel, 1983). Crelloxea was allocated in the marine sponge family Crellidae (Order Poecilosclerida), which is characterized by a tangential crust of spined ectosomal spicules (oxeas, anisoxeas or styles), a choanosomal plumose skeleton of smooth tornotes, sometimes a basal skeleton of acanthostyles erect on the substrate, microscleres usually arcuate chelae or absent, and surface with areolated pore fields (van Soest, 2002). Nowadays, Crelloxea is considered a junior synonym of Crella (Grayella) Carter, 1869 (van Soest, 2002; van Soest et al., 2015).